Performance assessment and system optimization on supercritical CO₂ double-path recompression coal-fired combined heat and power plants with MEA-based post-combustion CO₂ capture - Zhou, Jing (2023)
Combined heat and power (CHP) is the technical means to realize the joint and efficient production of thermal and electrical energy. This study aims to construct the performance analysis and system optimization methods of supercritical CO2 (S–CO2) coal-fired CHP plants with MEA-based post-combustion carbon capture and storage (CCS) that has adapted for various S–CO2 CHP cycles. S–CO2 recompression CHP cycle has imperfect adaptability and exhibits significant optimization potential based on energy and exergy analysis, as it shows substantial advantages over the S–CO2 power cycle. And S–CO2 double-path compression (DPR) coal-fired CHP plants have been proposed to decouple the system heating and power generation. Results show that exergy efficiency of S–CO2 DPR coal-fired CHP units at 0% and 100% heating loads (HL) are 43.22% and 46.21%, increasing by 9.81% and 1.01% compared with S–CO2 recompression CHP units, respectively. What is more advantageous is that S–CO2 DPR coal-fired CHP plant has the lower exergy efficiency decline (8.43% and 8.37% at 0% and 100% HL) with MEA-based CCS, showing more refined energy cascade utilization with heating supply, electricity generation and carbon capture. Sensitivity analysis of cycle maximum temperature and ion absorption technology is also performed, showing the excellent prospects of industrialization demonstration.